Calculation-Delay Tolerant Predictive Current Controller for Three-Phase Inverters - Fischer, Jonatan Roberto (2014)
This work presents an improved dead-beat predictive current controller for grid-tie inverters that addresses issues related to implementation delays. The total delay is composed of the integer computational delay and a fractional delay, which is taken into account in the design of the controller algorithm, to improve its performance and robustness. The control strategy, based on a model that includes these delays, employs state feedback and a prediction observer in order to obtain a true two-sample ripple free dead-beat response. System robustness can be adjusted with an appropriate selection of the location of the observer poles, at the expense of reducing control bandwidth. The proposed control scheme is both simple and computationally efficient since only few operations are required to include the delay in the algorithm. Experimental results show an improvement of the dynamic response even when mismatch in the load-inductance value estimation occurs.